How femtosecond laser irradiation can affect the gas sensing behavior of SnO2 nanowires toward reducing and oxidizing gases - Kim, Jae Hun; Park, Hyoungwon; Mirzaei, Ali; Hahm, Myung Gwan; Ahn, Sanghoon; Halik, Marcus; Park, Changkyoo; Kim, Sang Sub (Sensors and Actuators B-Chemical, 2021)
Generating oxygen vacancies on the metal oxides is an effective way to control their sensing properties. Furthermore, embossing surfaces are preferred to the flat surfaces for sensing studies due to providing of more adsorption sites, which is another key parameter for improvement of the gas sensing characteristics. In this study, we generated oxygen vacancies on SnO2 nanowires (NWs) by femtosecond (FS) laser irradiation with the different laser pulse energies of 0.025, 0.05, and 0.075 μJ, corresponding to the laser fluences of 138, 276, and 414 mJ/cm2. We investigated the effect of the FS laser irradiation on the response of the fabricated SnO2 NW gas sensors toward NO2 and toluene (C7H8) gases. The created oxygen vacancies and the response of the sensors were linked to the laser pulse energy. By studying the gas sensing characteristics of the sensors at various temperatures, we found that at 300 °C, the sensor irradiated at 0.025 μJ showed the highest response to C7H8, and the FS laser-irradiated sensors showed a lower response to the NO2 gas as compared to that of the non-irradiated sensor. The sensing mechanism of the gas sensors was comprehensively explained in terms of radial modulation of the SnO2 NWs, formation of SnO2 NW homojunctions, formation of embossing surfaces (increase of surface area) as well as formation of oxygen vacancies as a result of laser irradiation.
CRIS-Team Scopus Importer:2021-05-21
Keywords: Femtosecond laser irradiation; Gas sensor; NO; Sensing mechanism; SnO; Toluene